2005
DOI: 10.1159/000086461
|View full text |Cite
|
Sign up to set email alerts
|

BCG Immunization at Birth and Atopic Diseases in a Homogeneous Population of Spanish Schoolchildren

Abstract: Background: The role of immunization with bacillus Calmette-Guérin (BCG) in the prevalence of asthma, hay fever and atopic dermatitis is not definitely established and seems to be influenced by ethnic background. The aim of this study was to analyze the relationship between this immunization and the prevalence of those diseases in a homogeneous population of Spanish schoolchildren. Methods: The International Study of Asthma and Allergies in Childhood (ISAAC) core and environmental questionnaires were used in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…17 The main features of the 17 included studies are detailed in Table I. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Of particular note was that there was only 1 RCT 32 ; the remaining 16 studies used either cohort (n 5 7, 6 of which were retrospective and only 1 of which was prospective), 17,18,[22][23][24][26][27] case-control (n 5 2) 20,30 or cross-sectional (n 5 7) designs. 19,21,25,28,31,33 Sensitization to common allergens Ten studies investigated the relationship between BCG vaccination and allergic sensitization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The main features of the 17 included studies are detailed in Table I. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Of particular note was that there was only 1 RCT 32 ; the remaining 16 studies used either cohort (n 5 7, 6 of which were retrospective and only 1 of which was prospective), 17,18,[22][23][24][26][27] case-control (n 5 2) 20,30 or cross-sectional (n 5 7) designs. 19,21,25,28,31,33 Sensitization to common allergens Ten studies investigated the relationship between BCG vaccination and allergic sensitization.…”
Section: Resultsmentioning
confidence: 99%
“…18,19,[21][22][23][24][27][28][29]32 Analysis showed an overall OR of 0.84 (95% CI, 0.64-1.09) in the risk of eczema/atopic dermatitis (Fig 4); there was significant heterogeneity (I 2 5 89%). The funnel plot was suggestive of publication bias (see Fig E5 in Subgroup analysis was conducted to investigate the source of heterogeneity; analysis of children judged to be at high risk of allergic disorders found a similar effect size (OR, 0.81; 95% CI, 0.64-1.03; see Fig E7, A, in this article's Online Repository at www.jacionline.org).…”
Section: Eczema/atopic Dermatitismentioning
confidence: 98%
See 1 more Smart Citation
“…62,63 Moreover, BCG vaccination has been associated with a reduced allergic risk in some, but not all, human clinical trials. [64][65][66] In other investigations heat-killed Listeria species was found to be a potent adjuvant for the induction of T H 1-biased and the inhibition of T H 2-biased responses in mice and dogs. 67,68 Furthermore, rectal vaccination with heatkilled E coli expressing peanut allergen has been reported to reverse allergen-specific hypersensitivities in T H 2-sensitized mice.…”
Section: Tlr Ligand-containing Microbes and Atopymentioning
confidence: 93%
“…In developed countries, many studies found an absence of any relationship between BCG vaccination and atopic diseases in children (1011-1017) and young adults (1008). In other developing countries, there was a weak protective effect of BCG vaccination against asthma and hay fever (1018)(1019)(1020). In developing countries, an early BCG vaccination was associated with a weak prevention of atopic diseases (1009).…”
Section: Infections In the Neonatal Period And The Hygiene Hypothesismentioning
confidence: 99%